Association between hepatitis C virus infection and osteoporotic fracture risk among postmenopausal women: a cross-sectional investigation in Taiwan. Issue 1 (15th January 2019) - Lin, Ming-Shyan; Chen, Po-Han; Wang, Po-Chang; Lin, Huang-Shen; Huang, Tung-Jung; Chang, Shih-Tai; Chiu, Wen-Nan; Chen, Mei-Yen
Abstract : Purpose: Early low bone mass is a risk factor for osteoporotic fractures associated with multiple factors, including menopause and chronic liver diseases. Hepatitis C virus (HCV) also plays a major role in chronic liver disease and has many extrahepatic consequences, such as decreased bone mineral density (BMD). This study aimed to examine the hypothesis that HCV seropositivity is independently associated with menopausal BMD loss. Methods: This community-based, cross-sectional study was based in two rural townships in Yunlin County, Taiwan. A total of 636 menopausal women aged 45–80 years who underwent annual health checks were included. Viral markers of HCV, dual-energy X-ray absorptiometry and fracture risk assessment tool (FRAX) scores were measured. Logistic regression analysis was performed to assess the association between various predictors and the presence of low BMD. Results: The participants (median age: 65 years) had a HCV seropositivity rate of 32.2%. BMD was significantly lower in the HCV-seropositive participants in different anatomic locations than in the seronegative individuals (lumbar spine: −1.5 vs −1.1; total hip: −0.9 vs −0.6; femoral neck: −1.2 vs −1.0; p<0.05). HCV-seropositive subjects had higher rates of major osteoporotic fractures (11.3%±7.6%vs 9.0±6.8%; p<0.001) and hip fractures (3.4%±4.7%vs 2.3±4.9%; p=0.006) and a higher risk of lower BMD (osteopenia and osteoporosis) based on a multivariable regression analysis (adjusted OR: 1.8; 95% CI 1.16 to 2.81; p=0.009). Conclusions: HCV infection may be an independent risk factor for menopausal BMD loss and fractures predicted by FRAX.